2019
DOI: 10.1038/s41436-018-0381-1
|View full text |Cite
|
Sign up to set email alerts
|

ClinPhen extracts and prioritizes patient phenotypes directly from medical records to expedite genetic disease diagnosis

Abstract: Purpose: Diagnosing monogenic diseases facilitates optimal care, but can involve the manual evaluation of hundreds of genetic variants per case. Computational tools like Phrank expedite this process by ranking all candidate genes by their ability to explain the patient’s phenotypes. To use these tools, busy clinicians must manually encode patient phenotypes from lengthy clinical notes. With 100 million human genomes estimated to be sequenced by 2025, a fast alternative to manual phenotype extraction from clini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 35 publications
0
66
0
Order By: Relevance
“…It achieved more than 97% sensitivity on four network meta-analyses, decreasing the abstract review burden by 53% while only missing three of 124 eligible Evaluation (AMELIE) and ClinPhen, which can extract and prioritize candidate genes and patient phenotypes from literature and clinical notes. 34,35 However, none of these is like our procedure, which is designed specifically for gene-cancer penetrance studies and, as shown in this study, leads to a significant workload reduction in this context.…”
Section: Discussionmentioning
confidence: 96%
“…It achieved more than 97% sensitivity on four network meta-analyses, decreasing the abstract review burden by 53% while only missing three of 124 eligible Evaluation (AMELIE) and ClinPhen, which can extract and prioritize candidate genes and patient phenotypes from literature and clinical notes. 34,35 However, none of these is like our procedure, which is designed specifically for gene-cancer penetrance studies and, as shown in this study, leads to a significant workload reduction in this context.…”
Section: Discussionmentioning
confidence: 96%
“…Deisseroth et al from the same group developed ClinPhen. This algorithm parses clinical notes, converts them into a prioritized list of phenotypes, and eventually aids the diagnosis of rare genetic diseases . In addition, NLP has been used to find genomic relations with diseases in the medical literature and to assist with variant interpretation.…”
Section: Implementations Of Nlp In Clinical Genetics and Breast Cancementioning
confidence: 99%
“…In some cases, additional works are cited to provide context. A total of 15 articles were finally selected for inclusion [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: About the Paper Selectionmentioning
confidence: 99%
“…More recent efforts have demonstrated a high accuracy in identifying HPO terms in EHRs. ClinPhen [6] breaks EHR-derived free text into sentences and words, and uses heuristics to identify HPO terms in commonly encountered clinical phraseology. For instance, the phrase "Hands are large" will match the HPO term "Large hands (HP:0001176)", and excluded phenotypic abnormalities or those that were found in other family members are recognized as such.…”
Section: Identifying Phenotypic Abnormalities In Ehr Datamentioning
confidence: 99%